Cyclical Patterns in Government Health Expenditures between 1995 and 2010 : Are Countries Graduating from the Procyclical Trap or Falling Back? - Velenyi, Edit V.; Smitz, Marc F. (World Bank, Washington, DC, 2014)
The 2008-09 global economic crises have shown that no country is immune to external challenges. When policy controls are missing or not used efficiently, crises can reverse progress even in advanced economies. This unexpected outcome has increased concerns about the ability of governments in developing countries to manage downturns. The question is whether current and future crises will reinforce the procyclical responses or whether these governments will be able to escape the procyclical trap. In the fiscal domain, countercyclical trends in developing countries are promising. Over the last decade, about a third of the developing world has been able to escape the procyclicality trap. Yet, little is known about the evidence on the cyclical patterns of government health spending. This descriptive analysis, which covers 183 countries between 1995 and 2010, provides empirical evidence on the cyclicality of government health expenditures, using panel data from a global macro database, the fiscal health database. The objective is to propose user-friendly diagnostic approaches in this area that can be easily replicated and updated to inform technical discussions and policy making.